2010
DOI: 10.1038/onc.2010.565
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 (TACE) regulates TGFβ signaling through the cleavage of vasorin

Abstract: The activity of a variety of extracellular signaling factors is tightly regulated by proteins containing A Disintegrin And a Metalloprotease domain (ADAM) metalloproteases through limited proteolysis. Thus, the identification of ADAM substrates may unveil novel components and mechanisms of cell signaling pathways. We report the identification of the transmembrane protein vasorin (VASN), a transforming growth factor-b (TGFb) trap, as a substrate of ADAM17. The metalloprotease efficiently generates a soluble fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 30 publications
3
95
0
Order By: Relevance
“…Agtr1a , Epas1 , and Vasn are known to play roles in ovulation [48], [49], [50], [51], [52]. We have previously reported that follicular development is largely normal up to the antral stage but rarely reaches the preovulatory stage in the XY ovary [40], and very few or no oocytes are ovulated by XY females by gonadotropin treatment [53].…”
Section: Resultsmentioning
confidence: 99%
“…Agtr1a , Epas1 , and Vasn are known to play roles in ovulation [48], [49], [50], [51], [52]. We have previously reported that follicular development is largely normal up to the antral stage but rarely reaches the preovulatory stage in the XY ovary [40], and very few or no oocytes are ovulated by XY females by gonadotropin treatment [53].…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation of T cells with TGFb in the presence of IL-6 and sIL-6R led to more suppression of Treg cell differentiation than in the presence of IL-6 alone, indicating that IL-6 trans-signaling contributes to regulate the balance between Treg cells and Th17 cells [26]. The involvement of ADAM17 in this balance is further supported by the fact that TGFb activity is regulated by cleavage of vasorin, a protein that binds and neutralizes TGFb in its soluble but not in its cellbound form, thereby influencing the generation of regulatory T cells by TGFb [27]. These data show that ADAM17 activity influences various aspects of T cell biology.…”
Section: Reviewmentioning
confidence: 82%
“…Limited proteolysis by ADAM17 generates a soluble fragment encompassing the extracellular VASN domain, which directly binds to transforming growth factor (TGF)β and attenuates TGFβ signaling [100]. As in the case of ADAM10, ADAM17-dependent shedding has been demonstrated to be stimulated by thrombin [101].…”
Section: Resultsmentioning
confidence: 99%